Association of Soil-Transmitted Helminths Infection with Total Serum Immunoglobulin E Levels and Total Eosinophils in Elementary School Students in Medan - Siregar, Ren Amirah (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Soil-transmitted helminths infection is widespread in tropical and subtropical areas. More than 267 million preschool-aged children and more than 568 million school-age children live in areas where this parasite is transmitted intensively and requires treatment and prevention. People at risk are preschool children, school-aged children, reproductive age women, and adults in certain high-risk occupations, such as tea pickers or miners. Worm infections often infect elementary schoolchildren because at this time, children have many activities and are often in direct contact with a dirty environment so that it can cause children not to pay attention to personal hygiene. AIM: This study aimed to determine the association of STH infection with total serum IgE levels and eosinophil counts in elementary school students in Medan. METHODS: This cross-sectional study was conducted on 65 elementary school students at Medan orphanage who met inclusion and exclusion criteria. Examination of STH infection was carried out using Kato-Katz method, and blood tests were performed to assess total serum IgE and blood eosinophils counts. Univariate and bivariate analysis was performed to determine the association of STH infection with total serum IgE levels and eosinophil counts in these students using Pearson correlation test and Chi-square. RESULTS: Of the 65 elementary school students in the orphanage who were willing to have their routine blood and feces checked, 36 boys (55.3%) and 29 girls (44.6%), 39 children were infected with STH (60%). The most common infections were Ascaris lumbricoides (26.1%), Trichuris trichiura (18.4%), and mixed infections (15.3%) with an average of mild infection intensity. The results of the analysis showed that there was no significant association between STH infection and eosinophils counts (p = 0.582, 95% confidence interval, OR 1.3). In addition, there was also no significant association of STH infection with total serum IgE levels (p = 0.883, 95% confidence interval, OR 63.6). CONCLUSION: In this study, there was no association between STH infection with eosinophils counts and total serum immunoglobulin E levels in elementary school students in Medan.